Evaluation of Toxicity and Biodegradability of Cholinium Amino Acids Ionic Liquids - Hou, Xue-Dan; Liu, Qiu-Ping; Smith, Thomas J.; Li, Ning; Zong, Min-Hua (PloS one, 2013)
Cholinium amino acid ionic liquids ([Ch][AA] ILs), which are wholly composed of renewable biomaterials, have recently been demonstrated to have very promising properties for applications in organic synthesis and biomass pretreatment. In this work, the toxicity of these ILs toward enzymes and bacteria was assessed, and the effect of the anion on these properties is discussed. The inhibitory potentials of this type of ILs to acetylcholinesterase were weaker approximately an order of magnitude than the traditional IL 1-butyl-3-methylimidazolium tetrafluoroborate. Additionally, the [Ch][AA] ILs displayed low toxicity toward the bacteria tested. Furthermore, the biodegradability of the [Ch][AA] ILs was evaluated via the closed bottle and CO(2) headspace tests using wastewater microorganisms. All the ILs were classified as 'readily biodegradable' based on their high levels of mineralization (62-87%). The presence of extra carboxyl or amide groups on the amino acid side chain rendered the ILs significantly more susceptible to microbial breakdown. In addition, for most of the [Ch][AA] ILs, low toxicity correlated with good biodegradability. The low toxicity and high biodegradability of these novel [Ch][AA] make them promising candidates for use as environmentally friendly solvents in large-scale applications.